The Antidiabetic and Antinephritic Activities of Auricularia cornea (An Albino Mutant Strain) via Modulation of Oxidative Stress in the db/db Mice - Wang, Di; Jiang, Xue; Teng, Shanshan; Zhang, Yaqin; Liu, Yang; Li, Xiao; Li, Yu (Frontiers in Immunology, 2019)
This study first systematically analyzed the constituents of an albino mutant strain of Auricularia cornea (AU). After 8 weeks of continuous treatment with metformin (Met) (0.1 g/kg) and AU (0.1 and 0.4 g/kg), db/db mice showed hypoglycemic functioning, indicated by reduced bodyweight, food intake, plasma glucose, serum levels of glycated hemoglobin A1c and glucagon, hepatic levels of phosphoenolpyruvate carboxykinase and lucose-6-phosphatasem, and increased serum levels of insulin. The effect of hypolipidemic functions were indicated by suppressed levels of total cholesterol and triglyceride, and enhanced levels of hepatic glycogen and high-density lipoprotein cholesterol. The renal protective effect of AU was confirmed by the protection in renal structures and the regulation of potential indicators of nephropathy. The anti-oxidative and anti-inflammatory effects of AU were verified by a cytokine array combined with an enzyme-linked immunosorbent assay. AU decreased the expression of protein kinase C α and β2 and phosphor-nuclear factor-κB, and enhanced the expression of catalase, nuclear respiratory factor 2 (Nrf2), manganese superoxide dismutase 2, heme oxygenase-1 and−2, heat shock protein 27 (HSP27), HSP60, and HSP70 in the kidneys of db/db mice. The results confirmed that AU's anti-diabetic and anti-nephritic effects are related to its modulation on oxidative stress.